KAJIAN TUNDAAN LALU LINTAS PADA SIMPANG BERSINYAL (Studi Kasus: Simpang Jl. Brigjen Sudiarto - Jl. Majapahit - Jl. Fatmawati Kota Semarang) - Novianka P, Jayanti Rizqi; Hidayati, Khrisna Dwi; Supriyadi, Supriyadi; Junaidi, Junaidi (Politeknik Negeri Semarang, 2020)
Traffic volume in Semarang City has increased every year due to the increasing number of vehicles. Congestion that occurs at the T-junction intersection Jl. Brigjen Sudiarto - Jl. Majapahit is one of the impacts of high traffic growth and the traffic system is not functioning properly. By considering the geometric conditions of the road, traffic volume, side obstacles and the intersection environment which is a commercial area, it is necessary to analyze the cause of the congestion at the intersection. The research conducted was to conduct a field survey to obtain primary and secondary data which are then processed using intersection management. Planning uses the 1997 Indonesian Road Capacity Manual (MKJI) and uses the Excel 2013 program to process traffic data. Traffic data is obtained from recording the number of vehicles in the field for 3 days (April 29, 01 and May 4, 2019) during peak hours and presented in the form of a vehicle data table, then the behavior of the intersection can be analyzed. From the analysis results obtained value of the degree of saturation (DS) at the intersection of Jl. Brigjen Sudiarto - Jl. Majapahit 0.991. This value has exceeded the required value by the 1997 MKJI, DS â‰¤ 0.85. The analysis shows that the average traffic delay is 141,320 sec / pcu, so this intersection has a Service Level (LOS) F (> 60).